2013
DOI: 10.3174/ajnr.a3507
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Diffusion Tensor MR Tractography in Tuberous Sclerosis Complex: Correlation with Neurologic Severity and Tract-Based Spatial Statistical Analysis

Abstract: BACKGROUND AND PURPOSE:The neurologic significance of residual cerebral white matter tracts, identified on diffusion tensor tractography, has not been well studied in tuberous sclerosis complex. We aimed to correlate the quantity of reconstructed white matter tracts with the degree of neurologic impairment of subjects with the use of DTI and determined differences in white matter integrity between patients with tuberous sclerosis complex and controls with the use of voxelwise analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 40 publications
3
34
0
2
Order By: Relevance
“…Although there is no clear relationship between the extent and the degree of WM alterations and the clinical phenotype, there is some evidence that the more the WM is disrupted, the more severe the neurological phenotype might be [24,25,30]. Therefore, it is noteworthy to emphasize that we observed a statistically significant thinning of RNFL, even if our sample was constituted by patients who presented a relatively mild neurological phenotype.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Although there is no clear relationship between the extent and the degree of WM alterations and the clinical phenotype, there is some evidence that the more the WM is disrupted, the more severe the neurological phenotype might be [24,25,30]. Therefore, it is noteworthy to emphasize that we observed a statistically significant thinning of RNFL, even if our sample was constituted by patients who presented a relatively mild neurological phenotype.…”
Section: Discussionmentioning
confidence: 62%
“…The low fractional anisotropy frequently observed in neuroimaging studies of TSC strongly supports disorganized and poorly myelinated axons, while a primary poor integrity of the axons themselves is suggested by lower axial diffusivity [22,23]. Although an axonal involvement has been hypothesized after analyzing neuroimaging data [24,25], in humans, axonal structure has never been studied in detail before. Animal models showed that there is a primary axonal developmental defect caused by the genetic mutation in the TSC genes, which leads to a secondary myelination failure [26]; the TSC/mTOR pathway appears to limit multiple axon formation and acts to confine polarized growth within a single axon in the mammalian brain, and its deregulation likely contributes to the neurological symptoms commonly observed in TSC patients [8].…”
Section: Discussionmentioning
confidence: 94%
“…Based on the most recent neurological evaluation, each patient was assigned a score of neurological outcome (0ā€“8); the scoring method outlined by Wong et al . was used.…”
Section: Methodsmentioning
confidence: 99%
“…This finding is significant in that other investigators have found that abnormalities in FA in normal-appearing white matter correlate with the presence and severity of cognitive impairment in TSC patients. This suggests that mTOR inhibitors may reverse microscopic structural abnormalities, resulting in improved cognition and/or seizure control, in addition to effects on cortical tubers and SEGAs [51,52]. Furthermore, no patients developed new lesions or worsening hydrocephalus or required additional surgery intervention for SEGA during the evaluation phase of the trial or during the extension study [47,49].…”
Section: Pharmacotherapymentioning
confidence: 92%